Analysis of factors influencing students choosing vocational high school in Solok Selatan - Netra Surianto; Bustari Muchtar; Marwan Marwan (Universitas Negeri Padang, 2019)
This study aims to determine the factors that affect students choose smk country in the district south solok. The type of research is explorative research. The sampling technique in this study is with proportional random sampling, with a sample of 325 people who are distributed in 5 SMK Negeri Solok Selatan. Data collection was done through interviews, questionnaires, and documentation as a reference in this study. The analytical method used is factor analysis. Research is classified into quantitative research using survey method. To test the hypothesis by using t test. The results showed that: 1).Social Economy factors become factors that are considered by students to decide decisions in choosing a school. 2) cost of education and support factor becomes the factor considered by the students to determine the decision in choosing the school.